Images of Russians and Americans as Seen by Russian Adolescents - E. B. Marin (Вестник Кемеровского государственного университета, 2019)
The present research features the image of "the typical Russian" and "the typical American" as perceived by Russian adolescents  (students of the Far Eastern Federal University). The images were  reconstructed using methods of psychosemantics, e.g. verbal  associations. The data were processed using the methods of  mathematical statistics. The semantic analysis helped to define the  ideas and emotional attitude of the respondents to "the typical  Russian" and "the typical American", as well as the semantic  contrast of the content in some categories. The Fisher criterion  revealed significant differences in the content of certain categories of associations. The stereotype displayed a predominantly positive  orientation, while the orientation of the heterostereotype was  ambivalent. The image of "the typical Russian" reflected primarily  such positive qualities as kindness, openness, and patriotism. Both  positive (activity, tact) and negative qualities (hypocrisy and lies)  were manifested in the ideas about the "typical American". The  positive personal characteristics included activity, charisma, and  communicative skills. However, the personal qualities of the  "American" clearly expressed some negative traits, e.g. hypocrisy  and lies. The generalized  image of "the typical American" is  outwardly pleasant, active, and sociable but internally hypocritical,  deceitful and selfserving. The content of the heterostereotype  reflected a certain distrust of young people to "the typical American". The negative characteristics of the heterostereotype may reduce  tolerance of young people to the USA and its representatives. The  results of the study may be useful to representatives of public  authorities and educational institutions. The obtained data can be  used to shape multicultural educational environment in Russian  universities.